Session builders series 300 : 50 exercises for teams (HRD Press, 2010)
Getting a team to gel, produce and be successful is never easy. Invariably, you'll have team members who are inflexible or oversensitive ... talk too much or stay silent ... point fingers or stir up conflict. These 50 exercises are a terrific way to confront these and other issues you may be facing as a team leader. And you can implement any and all of them quickly, without a big budget and with little or no training experience.